Analisis Koreksi Fiskal Terhadap Laporan Keuangan Komersial Pada PT. Thermoplast Indo - Louis, Purnamawati Helen Widjaja (Jurnal Paradigma Akuntansi, 2021)
The object of this study was PT. Thermoplast Indo, it provide service or sparepart for heavy lifting equipment. The purpose of this research is to determine company debt of income tax value by doing reconciliation of commercial financial report to be fiscal financial report. By doing reconciliation company doesn’t have to make two reports with different purposes. Company only has to make correction towards different accounts. Positive correction will add taxable income while negatice income will reduce taxable income.Based on the result of the analysis that has been done by the author and comparing with the commercial financial report with report of fiscal rules that are based on tax law Number 36 year 2008 the amount of profit  generated is different. This difference occurs because the fiscal correction is done against the cost and earnings in commercial financial reports based on taxation.